Talking stone rock art of the Cosos - Goldsmith, Paul (The University of Utah Press, 2017)
"This book acts as a visual vehicle to see the rock art of the Coso Range. The Coso Range sits on the edge of the Mojave Desert, just east of the Sierra Nevada. It is located within the 1.2 million acres Naval Air Weapons Station (NAWS) China Lake and contains distinctive and spectacular displays of rock art. This rock art fills the lava gorges of Renegade Canyon, Big Petroglyph Canyon, and Sheep Canyon with images of bighorn sheep, anthropomorphs, abstract geometric figures and shield-like figures. These are pecked into the dark basalt and most appear to be between 1000 to 3000 years old, although some may be older and date to the earliest occupation of the region roughly 13,000 years ago. Both the text and photography are by Paul Goldsmith, an acclaimed cinematographer. This project is highly visual in nature and provides a photographic tour of the canyons and rock art for those that will never have a chance to visit them"--Provided by publisher
Keywords: Vor- und Frühgeschichte; Felsbild; Coso-Formation; USA; Panamint Indians / California / Coso Range / Antiquities; Petroglyphs / California / Coso Range; Coso Range (Calif.) / Antiquities; Rock paintings / California / Coso Range; Indian art / California / Coso Range; Bildband